Two concepts of community in the Niger Delta: Social sense of communality, and a geographical sense of place. Are they compatible?. Issue 3 (14th August 2017) - Okeke-Ogbuafor, Nwamaka; Gray, Tim; Stead, Selina
Abstract : Purpose: This paper aims to understand what two apparently contrasting concepts of communality and place attachment say about the quality of community life in the Niger Delta. Design/methodology/approach: The research for this paper relied on extensive qualitative and quantitative data: qualitative data were collected from five oil-rich and three oil-poor communities across Ogoniland, while quantitative data were collected from four of these communities. Thematic content analysis was used to interpret the qualitative data, while the quantitative data were analysed through Excel. Findings: Most participants from both oil-rich and oil-poor communities strongly reject a social sense of communality and strongly endorse a geographical sense of place. Practical implications: The wider implication of this finding is that proponents of community development (CD) have a choice between either the cynical option of noting that Ogoni's strong sense of place means that they will tolerate limited CD, or the noble option of noting that Ogoni's strong sense of place is a solid foundation on which to build sustainable CD by empowering citizens to create their own future. Originality/value: The originality of this study is twofold. First, it shows the complexity of people's sense of community encompassing widely different and possibly contradictory elements. Second, it reveals the strength and persistence of people's attachment to place despite its physical shortcomings.